2015
DOI: 10.1017/prp.2015.10
|View full text |Cite
|
Sign up to set email alerts
|

Under the Dome: Air Pollution, Wellbeing, and Pro-Environmental Behaviour Among Beijing Residents

Abstract: T he conflict between economic development and environmental protection has been made salient by increasingly severe air pollution in China, a visible consequence of the costs of rapid economic progress. How does air pollution affect people's psychological experiences? How are newly rich Chinese beginning to think about this social dilemma and are they willing to take any action to deal with the problem? Are there individual differences that contribute to the effect of air pollution on mental experience and co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 67 publications
1
24
0
Order By: Relevance
“…Therefore, they are more likely to engage in local and global actions. Finally, Gu, Huang, Zhang, and Wang () postulated that place attachment leads people to experience a higher sense of meaning and purpose in life and thus stimulate eudemonic well‐being. It may also improve people's willingness to engage in general pro‐environmental behaviors.…”
Section: Place Attachmentmentioning
confidence: 99%
“…Therefore, they are more likely to engage in local and global actions. Finally, Gu, Huang, Zhang, and Wang () postulated that place attachment leads people to experience a higher sense of meaning and purpose in life and thus stimulate eudemonic well‐being. It may also improve people's willingness to engage in general pro‐environmental behaviors.…”
Section: Place Attachmentmentioning
confidence: 99%
“…Positive environmental attitude often means that an individual identifies the sacrifice of short‐term interests to protect long‐term benefits. Previous studies have found that future orientation was consistently and positively related to general environmental attitudes, pro‐environmental behaviour intentions and involvement in pro‐environmental activities (e.g., Gu, Huang, Zhang, & Wang, ; Milfont et al, ). Therefore, when individuals scoring high on the Dark Triad traits encounter the trade‐offs between short‐term interests and future environmental benefits, they might tend to satisfy their immediate interests at the expense of the future environment due to their low level of future orientation, which is eventually expressed as negative environmental attitudes.…”
Section: The Dark Triadmentioning
confidence: 92%
“…Vorkinn and Riese () found that place attachment positively predicted attitudes about local environmental issues. Research has also indicated that place attachment was positively associated with a series of pro‐environment behaviours, including picking up litter in the park, protecting natural landscapes and fighting against air pollution (e.g., Gu et al, ; Walker & Ryan, ). Therefore, we predicted that the Dark Triad traits were associated with environmental attitudes through place attachment.…”
Section: The Dark Triadmentioning
confidence: 99%
“…Understanding the effects of haze-fog on human health is important for enhancing people's well-being in a rapidly urbanizing country [14]. Although the findings are very encouraging, there are still some limitations.…”
Section: Introductionmentioning
confidence: 99%